PENGEMBANGAN BAHAN AJAR ELEKTRONIK PEMBELAJARAN MATEMATIKA BERBASIS PROBLEM BASED LEARNING DENGAN MENGGUNAKAN APLIKASI FLIP PDF PROFESSIONAL DI SEKOLAH DASAR - Nindya Pratiwi; Yantoro; Syahrial (Cerdas Proklamator, 2024)
This research aims to produce electronic teaching materials for Mathematics learning based on Problem Based Learning on fractions for fourth grade elementary school students. This type of research is development research (Research and Development). The research includes validity sheets and practicality sheets (teacher and student response questionnaires). The validator consists of 3 expert lecturers, namely material, language and design validators. Based on the teaching materials that have been developed, the validation of electronic teaching materials which was carried out from the material aspect obtained a validity percentage of 90% with very valid criteria, from the language aspect obtained a validity percentage of 90.62% with very valid criteria and from the design aspect obtained a validity percentage of 88.15 % with valid criteria. Judging from the average validity of the teaching materials that have been developed, they meet the valid criteria with a validity percentage of 89.59%. The practicality test consisted of 1 class teacher and 25 students. From the results of the teacher's responses, a practicality percentage of 98% was obtained with very practical criteria and the results of responses by students were obtained with a practicality percentage of 92.25% with very practical criteria. Based on the research results, it can be concluded that electronic teaching materials for Mathematics learning based on Problem Based Learning meet valid and practical criteria that can be used in class IV mathematics learning in elementary schools.